2016
DOI: 10.1002/jssc.201600437
|View full text |Cite
|
Sign up to set email alerts
|

Identification and screening of chemical constituents with hepatoprotective effects from three traditional Chinese medicines for treating jaundice

Abstract: The constituents with hepatoprotective activity were investigated in three traditional Chinese medicine formulae for treating jaundice, namely, Zhi-Zi-Da-Huang-Tang, Yin-Chen-Hao-Tang, and Da-Huang-Xiao-Shi-Tang. By using liquid chromatography coupled with quadrupole time-of-flight mass spectrometry and liquid chromatography coupled with ion trap mass spectrometry, 79 chemical constituents were identified unambiguously or tentatively in three formulae based on the accurate molecular weight, mass spectrometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Groenlandicine exhibited moderate inhibitory effects on anti-diabetic complications [ 16 ] and anti-Alzheimer effect [ 17 ], and it was also identified as an active principle with topoisomerase I-mediated DNA cleavage activity in vitro [ 18 ]. Jatrorrhizine exerted hepatoprotective activities [ 19 ], neuroprotective activity [ 20 ] and antihypercholesterolemic activity [ 21 ]. Palmatine had the third highest content of alkaloids in RC, and it was proven to have anti-bactericidal activity against H. pylori in vitro and in vivo [ 22 ], gastroprotective effect against gastric ulcers [ 23 ], heartprotective activity against acute myocardial injury [ 24 ] and memory-enhancing activity [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Groenlandicine exhibited moderate inhibitory effects on anti-diabetic complications [ 16 ] and anti-Alzheimer effect [ 17 ], and it was also identified as an active principle with topoisomerase I-mediated DNA cleavage activity in vitro [ 18 ]. Jatrorrhizine exerted hepatoprotective activities [ 19 ], neuroprotective activity [ 20 ] and antihypercholesterolemic activity [ 21 ]. Palmatine had the third highest content of alkaloids in RC, and it was proven to have anti-bactericidal activity against H. pylori in vitro and in vivo [ 22 ], gastroprotective effect against gastric ulcers [ 23 ], heartprotective activity against acute myocardial injury [ 24 ] and memory-enhancing activity [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Narirutin, naringin, hesperidin, and neohesperidin, the active constituents of ZS, could inhibit pro-in ammatory factors, attenuate liver damage, modulate the state of antioxidants, and have hypoglycemic and hypolipidemic effects [44][45][46][47]. Some studies have revealed that the major iso avonoids of DDC, such as daidzein, have a signi cant hepatoprotective effect against oxidative damage induced by tert-butylhydroperoxide (TBHP) in rat hepatocyte BRL-3A cell line, which is closely related to the e cacy of ZZDHD [15,16,18]. Some pharmacokinetics indicated that iso avone glycosides of DDC, including daidzein and genistin, could be hydrolyzed in the intestinal wall by bacterial β-glucosidases after oral administration, and further transformed into corresponding bioactive aglycones, and all of them could be excreted into bile [48].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, TCM is administered as formula, which is prescribed in combination of several medicinal herbs at a certain mass ratio . Revealing the scientific foundation of TCM formulas; such as, the chemical constituents, metabolic pathways, active constituents responsible for pharmacological effects, and synergistic action of multiconstituents, can establish a bridge between TCM theories and modern science, promoting the modernization and globalization of TCM . However, due to the complexity, the chemical constituents and metabolic profiling of most TCM formulae remain unclear, which urgently needs systemic investigation.…”
Section: Introductionmentioning
confidence: 99%